Pagination versus scrolling in mobile web search - Kim, Jaewon; Thomas, Paul; Sankaranarayana, Ramesh; Gedeon, Tom; Yoon, Hwan-Jin (Proceedings of the International ACM SIGIR Conference on on Information and Knowledge Management, 2016)
Vertical scrolling is the standard method of exploring search results pages. For touch-enabled mobile devices that are not equipped with a mouse or keyboard, we adopt other methods of controlling the viewport with the aim of investigating user interaction. From the intuition that people are used to reading books by turning pages horizontally, we conducted a user experiment to investigate the effects of horizontal and vertical control types (pagination versus scrolling) on a touch-enabled mobile phone. Our ﬁndings suggest that participants using pagination were more likely to find relevant documents, especially those over the fold; spent more time attending to relevant results; and were faster to click while spending less time on the search result pages overall. We also found that the main reason for the difference in search speed is the time taken for the scroll itself. We conclude that search engines need to provide different viewport controls to allow better search experiences on touch-enabled mobile devices.